Magnetic hydrophobic material Fe3O4 (at) PDA-HDTMS and application thereof in removing micro-nano plastic in water body
By developing the magnetic hydrophobic material Fe3O4@PDA-HDTMS, the problem of low efficiency and high cost of removing PE and PP MNPs in the prior art is solved, and an efficient, economical and environmentally friendly removal effect is achieved.
Patent Information
- Application Number
- CN202411867369.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-01
AI Technical Summary
The prior art is inefficient, costly, and may cause secondary pollution to the environment when removing polyethylene (PE) and polypropylene (PP) micro-nano plastics (MNPs).
A magnetic hydrophobic material Fe3O4@PDA-HDTMS was developed to remove PE and PP MNPs in water by preparing Fe3O4 microspheres, Fe3O4@PDA microspheres and Fe3O4@PDA-HDTMS microspheres.
It has achieved efficient removal of PE and PP MNPs, with a removal rate of 92.7% to 93.8%, and has shown good stability and adaptability under various environmental conditions.
Smart Images

Figure CN119733486A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a magnetic hydrophobic material Fe3O4@PDA-HDTMS and application thereof in removing micro-nano plastics in water, belonging to the technical field of adsorption materials. Background Art
[0002] Plastic is a synthetic polymer composed of hundreds to thousands of organic monomers connected by strong covalent bonds. Over time, large plastic waste may break down into smaller fragments, including microplastics (MPs, particle size <5mm) and nanoplastics (NPs, particle size <1000nm). These micro-nanoplastics (MNPs) are potentially harmful to aquatic life and human health.
[0003] MPs usually tend to settle on the seafloor and gradually accumulate, while NPs, due to their high buoyancy, are often suspended in the water and spread rapidly under the action of ocean currents. In addition, MNPs can adsorb toxic chemicals in the environment due to their high surface area to volume ratio. These adsorbed harmful substances may be transferred through the food chain, posing a serious threat to human health. The main routes of human exposure to MNPs include ingestion, inhalation and skin absorption. At present, the scientific community has detected MNPs in human blood, lungs, placenta, endometrium, and metabolites in feces. Although no convincing evidence of adverse effects of MNPs on human health has been found, it is clear that humans are being exposed to MNPs. Studies have shown that MNPs can enter the human circulatory system and cause systemic exposure, and bring health hazards, including inducing oxidative stress, inflammation and cell damage. Among them, NPs are of particular concern because their small size enables them to penetrate biological barriers and may accumulate in organs and tissues, causing toxicity.
[0004] Therefore, there is an urgent need to solve the widespread problem of plastic pollution, especially the spread of MNPs in the environment and its potential hazards. At present, the removal technology of MNPs has become a hot topic in global research. Polystyrene (PS) plastics have become the focus of removal technology research due to their wide application and structural characteristics. For the removal methods of PS, many studies have involved physical adsorption, chemical degradation and biodegradation, which can effectively remove PS in the environment under certain conditions. However, there are relatively few studies on the removal of polyethylene (PE) and polypropylene (PP) plastics. PE and PP, as the most common types of plastics, are widely present in daily consumer products such as plastic bags, bottles, packaging films and food containers. Due to their strong chemical stability and low density, PE and PP are more difficult to handle than PS MPs. PE and PP MNPs degrade slowly in the natural environment, and due to their special chemical structure, traditional physical and chemical removal methods are difficult to effectively achieve removal or degradation.
[0005] Although a small number of studies have attempted to develop removal technologies for PE and PP MPs, existing methods generally face problems such as low efficiency, high cost and possible secondary pollution to the environment. Currently, the technology for removing PE and PP MPs is still in a relatively preliminary stage, lacking efficient, economical and sustainable solutions that can be widely promoted in practical applications. Summary of the invention
[0006] [Technical issues]
[0007] Existing methods for removing PE and PP MPs generally face problems such as low efficiency, high cost and possible secondary pollution to the environment.
[0008] [Technical solution]
[0009] In order to solve the defects and shortcomings of the prior art, the purpose of the present invention is to achieve efficient removal of PE and PP MNPs while achieving PS plastic removal through innovative adsorption material design and process optimization. The material not only has good adaptability and practicality, but also can operate stably under a variety of environmental conditions, and has a good removal rate for PE and PP nano-scale plastics in aqueous solution. This provides a new technical approach to solve the pollution problem of PE and PP plastics.
[0010] In order to achieve the above purpose, the technical solutions provided are as follows:
[0011] The first object of the present invention is to provide a method for preparing a magnetic hydrophobic material Fe3O4@PDA-HDTMS for adsorbing MNPs, the preparation method comprising the following steps:
[0012] (1) Preparation of Fe3O4 microspheres
[0013] FeCl3·6H2O, ammonium acetate (NH4Ac), sodium citrate and ethylene glycol are mixed in a flask, and mechanically stirred to completely mix to obtain a yellow solution; the yellow solution is sealed in a high-pressure reactor to react; after the reaction, it is cooled, washed, magnetically separated and dried to obtain Fe3O4 microspheres;
[0014] (2) Preparation of Fe3O4@PDA microspheres
[0015] The magnetic Fe3O4 microspheres prepared in step (1) are added with Tris buffer, mechanically stirred, and then dopamine (DA) is added, and the reaction is continued by stirring, magnetic separation is performed, and the synthetic product Fe3O4@PDA is collected, washed, magnetically separated, and dried to obtain Fe3O4@PDA microspheres;
[0016] (3) Preparation of Fe3O4@PDA-HDTMS microspheres
[0017] HDTMS and the Fe3O4@PDA microspheres prepared in step (2) are added to a container containing a methanol solution and continuously stirred for reaction; the synthesized product is collected, washed, magnetically separated, and dried to obtain a magnetic hydrophobic material Fe3O4@PDA-HDTMS, i.e., Fe3O4@PDA-HDTMS microspheres.
[0018] In one embodiment, the mass ratio of FeCl3·6H2O to ammonium acetate in step (1) is 1.35:(3.6-4), and can be specifically 1.35:3.85.
[0019] In one embodiment, the mass ratio of FeCl3·6H2O to sodium citrate in step (1) is 1.35:(0.2-0.6), and can be specifically 1.35:0.4.
[0020] In one embodiment, the mass volume ratio of the FeCl3·6H2O and ethylene glycol in step (1) is 1.35 g: (60-80) mL, and can be specifically 1.35 g: 70 mL.
[0021] In one embodiment, the reaction conditions in the high-pressure reactor in step (1) are: temperature of 180-200° C., and reaction time of 16-24 h.
[0022] In one embodiment, the washing in step (1) is performed by alternating ultrapure water and anhydrous ethanol, and specifically, the ultrapure water is washed 3 to 5 times and the anhydrous ethanol is washed 3 to 5 times.
[0023] In one embodiment, the mass volume ratio of the Fe3O4 microspheres and the Tris-HCl buffer solution in step (2) is 80 mg: (30-50) mL, and can be specifically 80 mg: 40 mL.
[0024] In one embodiment, the pH of the Tris-HCl buffer solution in step (2) is 8.5 and the concentration is 0.01 mol / L.
[0025] In one embodiment, the mass ratio of Fe3O4 and DA in step (2) is 1:1.
[0026] In one embodiment, the stirring reaction conditions in step (2) are as follows: the temperature is 25 to 30° C. and the time is 12 to 24 hours.
[0027] In one embodiment, the washing in step (2) is performed by alternating ultrapure water and anhydrous ethanol, and specifically, washing with ultrapure water for 3 to 5 times and washing with anhydrous ethanol for 3 to 5 times.
[0028] In one embodiment, the mass volume ratio of Fe3O4@PDA and HDTMS in step (3) is 60 mg: (0.45-0.6) mL, and can be specifically 60 mg: 0.5 mL.
[0029] In one embodiment, the purity of the HDTMS in step (3) is industrial grade, >85%.
[0030] In one embodiment, the volume of the methanol solution in step (3) is 25-30 mL.
[0031] In one embodiment, the continuous stirring reaction conditions in step (3) are: temperature of 25 to 30° C. and time of 12 to 24 hours.
[0032] In one embodiment, the washing in step (3) is performed by alternating ultrapure water and anhydrous ethanol for more than 6 times, and specifically, the ultrapure water is used for 3 times and the anhydrous ethanol is used for 3 times.
[0033] The second object of the present invention is to provide a magnetic hydrophobic material Fe3O4@PDA-HDTMS obtained by the above preparation method.
[0034] The third object of the present invention is to provide the use of the above-mentioned magnetic hydrophobic material Fe3O4@PDA-HDTMS in removing pollutants in water.
[0035] The fourth object of the present invention is to provide a method for removing MNPs in water based on the magnetic hydrophobic material Fe3O4@PDA-HDTMS, the method being as follows:
[0036] The magnetic hydrophobic material Fe3O4@PDA-HDTMS is placed in water for stirring, magnetic separation, and collection of the magnetic hydrophobic material Fe3O4@PDA-HDTMS.
[0037] In one embodiment, the water body is filtered through a glass fiber filter membrane to remove large particles.
[0038] In one embodiment, the water body is one or more of bottled drinking water, tap water and sea water.
[0039] In one embodiment, the glass fiber filter has a pore size of 1 μm and a diameter of 25 mm.
[0040] In one embodiment, the concentration of the magnetic hydrophobic material Fe3O4@PDA-HDTMS is 1.3-1.7 mg / mL, and specifically can be 1.5 mg / mL.
[0041] In one embodiment, the stirring conditions are: 20-30° C., 100-200 rpm, 20-40 min.
[0042] In one embodiment, the separation is performed by separating the solid and liquid phases using an external magnet.
[0043] In one embodiment, the MNPs include one or more of polystyrene (PS), polyethylene (PE) and polypropylene (PP) plastics; preferably one or two of polyethylene (PE) and polypropylene (PP) plastics.
[0044] A fifth object of the present invention is to provide a method for improving the removal rate of polyethylene plastics and / or polypropylene plastics in water, the method comprising the following steps:
[0045] The magnetic hydrophobic material Fe3O4@PDA-HDTMS is placed in water for stirring, magnetic separation, and collection of the magnetic hydrophobic material Fe3O4@PDA-HDTMS.
[0046] Beneficial effects of the present invention:
[0047] (1) The magnetic hydrophobic material Fe3O4@PDA-HDTMS prepared by the present invention has a very wide range of application value. The presence of DA enhances the dispersibility of HDTMS after DA self-polymerization. The long alkyl chain and super hydrophobicity of HDTMS molecules enable it to specifically adsorb PE and PP as well as PS MNPs in aqueous solution.
[0048] (2) The Fe3O4@PDA-HDTMS magnetic hydrophobic material prepared by the present invention can be saturated with adsorption within 25 to 30 minutes, and the removal rates of PE-MPs, PP-MPs, and PS-MPs are 92.7% to 93.8%, with RSDs <5.5%; the removal rates of PE-NPs, PP-NPs, and PS-NPs are 82.2% to 87.2%, with RSDs <3.7%; in addition, the removal rates of the three MNPs of PE, PP, and PS after mixing are respectively 93.5% at the micron level, with RSD = 5.1%; and 84.8% at the nano level, with RSD = 0.9%, indicating that the method of the present invention can effectively adsorb a variety of MNPs in the water environment. It provides a simple and quick method for the control and removal of MNPs in the water environment and drinking water. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is a schematic diagram of the principle structure of Fe3O4@PDA-HDTMS microspheres prepared in Example 1;
[0050] Figure 2This is a scanning electron microscope image of the Fe3O4@PDA-HDTMS microspheres prepared in Example 1;
[0051] Figure 3 This is a transmission electron microscopy image of the Fe3O4@PDA-HDTMS microspheres prepared in Example 1;
[0052] Figure 4 This is the Fourier transform infrared spectrum of Fe3O4@PDA-HDTMS microspheres prepared in Example 1;
[0053] Figure 5 The X-ray diffraction spectrum of Fe3O4@PDA-HDTMS microspheres prepared in Example 1;
[0054] Figure 6 This is an X-ray photoelectron spectrometer image of Fe3O4@PDA-HDTMS microspheres prepared in Example 1;
[0055] Figure 7 The hysteresis loop diagram of Fe3O4@PDA-HDTMS microspheres prepared in Example 1;
[0056] Figure 8 This is the EDX characterization image of Fe3O4@PDA-HDTMS microspheres prepared in Example 1;
[0057] Fig. 9 This is the water contact angle diagram of Fe3O4@PDA-HDTMS microspheres prepared in Example 1;
[0058] Fig.10 This is the mechanism diagram of the adsorption of MNPs by Fe3O4@PDA-HDTMS microspheres in Example 2;
[0059] Fig.11 This is a diagram showing the actual process of Fe3O4@PDA-HDTMS microspheres adsorbing MNPs in Example 2;
[0060] Fig.12 This is the optical image of Fe3O4@PDA-HDTMS microspheres adsorbing MNPs in Example 2;
[0061] Fig.13 This is the data graph of the removal rate of different types of MNPs by Fe3O4@PDA-HDTMS microspheres in Example 3;
[0062] Fig.14 It is the data graph of the removal rate of different MNPs by Fe3O4, Fe3O4@PDA and Fe3O4@PDA-HDTMS microspheres in Comparative Example 1;
[0063] Fig.15This is a data graph of the removal efficiency of Fe3O4@PDA-HDTMS microspheres for different types of MPs in Comparative Example 2. DETAILED DESCRIPTION
[0064] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention. The following specific implementation methods further describe the present invention.
[0065] Sources of materials involved in this invention:
[0066] MNPs standard, hexadecyltrimethoxysilane (HDTMS, industrial grade, >85%, Sigma-Aldrich, catalog no. 52360), dopamine (98%), FeCl3·6H2O (99%).
[0067] PE-500, PP-500, and PS-500 involved in the embodiments are abbreviations of PE, PP, and PS particles with a size of 500 nm, and PE-5000, PP-5000, and PS-5000 involved are abbreviations of PE, PP, and PS particles with a size of 5000 nm.
[0068] Example 1
[0069] A method for preparing a magnetic hydrophobic material Fe3O4@PDA-HDTMS comprises the following steps:
[0070] (1) Preparation of Fe3O4 microspheres
[0071] The magnetic Fe3O4 microspheres were synthesized by the solvent thermal reduction method: specifically, FeCl3·6H2O (1.35 g), NH4Ac (3.85 g), sodium citrate (0.4 g) and ethylene glycol (70 mL) were mixed in a flask, and mechanically stirred vigorously for 1 h to obtain a yellow solution; the obtained yellow solution was sealed in a 100 mL Teflon-lined autoclave, and placed in an oven at 200°C for 16 h, and after cooling to room temperature, the Fe3O4 magnetic microspheres were collected by magnetic separation (with an external magnet), and then washed alternately with ultrapure water and anhydrous ethanol, and dried in a vacuum drying oven at 60°C for 12 h to obtain the magnetic Fe3O4 microspheres;
[0072] (2) Preparation of Fe3O4@PDA microspheres
[0073] Take 80 mg of the Fe3O4 microspheres obtained in step (1) and add 40 mL of Tris buffer (10 -2mol / L, pH=8.5) and mechanically stirred for 20 min, then 80 mg of dopamine (DA) was transferred to the above solution and stirred continuously for 24 h. Finally, the synthesized product Fe3O4@PDA was collected by magnetic separation (with an external magnet), washed alternately with ultrapure water and anhydrous ethanol, magnetically separated and dried to obtain Fe3O4@PDA microspheres.
[0074] (3) Preparation of Fe3O4@PDA-HDTMS microspheres (schematic diagram as shown in Figure 1 (shown)
[0075] Take 0.5 mL of hexadecyltrimethoxysilane (HDTMS: industrial grade, >85%, Sigma-Aldrich, catalog no. 52360) and 60 mg of Fe3O4@PDA microspheres synthesized in step (2), add them to a glass containing 30 mL of methanol solution, and shake them on a magnetic vortex mixer at room temperature overnight (12 h) to react; finally, collect the synthesized product Fe3O4@PDA-HDTMS by magnetic separation (external magnet), rinse it alternately with ultrapure water and anhydrous ethanol several times, and dry it at 60°C for 12 h to obtain Fe3O4@PDA-HDTMS microspheres, which are stored at low temperature.
[0076] Performance Characterization
[0077] The magnetic microspheres Fe3O4 and Fe3O4@PDA and the magnetic hydrophobic material Fe3O4@PDA-HDTMS prepared in Example 1 were characterized as follows:
[0078] The surface of Fe3O4@PDA-HDTMS magnetic nanospheres was characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM) and Fourier transform infrared spectrometer (FT-IR) to verify the existence of certain characteristic functional groups and the synthesis of specific chemical bonds; X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) were used to qualitatively analyze the surface elements of Fe3O4@PDA-HDTMS and the structure and molecular crystal form of chemical valence bonds; the magnetic properties of Fe3O4, Fe3O4@PDA and Fe3O4@PDA-HDTMS were determined by vibrating sample magnetometer (VSM) method at a magnetic field scanning intensity of -2T-2T and a temperature of 300K; Fe3O4@PDA-HDTMS was characterized by EDX, the main elements and contents in the sample were tested, and the water contact angle of Fe3O4@PDA-HDTMS microspheres was analyzed.
[0079] The results are as follows Figure 2-9 As shown, Figure 2 This is the SEM characterization image of Fe3O4@PDA-HDTMS. It can be observed that Fe3O4@PDA-HDTMS is a spherical nanoparticle with a rough surface. Figure 3 This is the TEM characterization image of Fe3O4@PDA-HDTMS. A clear shadow layer can be clearly seen on the outer layer of the Fe3O4@PDA-HDTMS particles, proving that the material has a core-shell structure. Figure 4-6 Characterizing the chemical bonds, molecular crystal forms, and chemical bonding in a material can help determine the successful synthesis of the material. Figure 7 It is a characterization of the magnetic properties of the material. It can be found that with the successive coating of PDA and HDTMS, the magnetism of the composite material will decrease accordingly. This is a normal phenomenon. In addition, it is found that the magnetism of Fe3O4@PDA-HDTMS is very good, which meets the experimental requirements. Figure 8 This is the EDX curve of Fe3O4@PDA-HDTMS material, which proves that as the material is synthesized, its surface elements will also increase. Finally, Fe3O4@PDA-HDTMS material contains Fe, C, O, N, Si and other elements, indicating that the material was successfully synthesized. Fig. 9 It can be found that the water contact angle of Fe3O4@PDA-HDTMS is 139.6°, indicating that it has strong hydrophobicity, which can be attributed to the presence of HDTMS hydrophobic long chains on its surface. All characterization results show that the material was successfully synthesized and has excellent magnetic properties and strong hydrophobicity.
[0080] Example 2
[0081] A method for removing MNPs from water based on Fe3O4@PDA-HDTMS microspheres, specifically comprising the following:
[0082] PE-500NPs, PE-5000MPs, PP-500NPs, and PP-5000MPs were prepared into suspensions in water with a concentration of 2 mg / mL, and the suspensions were ultrasonically treated for 30 min. Then, 15 mg of the Fe3O4@PDA-HDTMS magnetic hydrophobic material prepared in Example 1 was added to 10 mL of the above suspensions and shaken at 120 rpm for 30 min at room temperature (adsorption mechanism as shown in Fig.10 shown).
[0083] The adsorption process is Fig.11 As shown. There are a large number of PE-500NPs, PE-5000MPs, PP-500NPs, and PP-5000MPs in the suspension before adsorption, and there are almost no MNPs particles after adsorption. It can be seen that the turbid suspension becomes transparent during the adsorption process, indicating that a large number of MNPs are rapidly adsorbed by Fe3O4@PDA-HDTMS. In addition, as Fig.12 As shown, the optical images of the solution before and after absorption also proved that these MNPs were adsorbed by Fe3O4@PDA-HDTMS.
[0084] Example 3
[0085] A method for removing MNPs based on Fe3O4@PDA-HDTMS microspheres, specifically comprising the following:
[0086] (1) PE-500NPs, PP-500NPs, PS-500NPs, PE-5000MPs, PP-5000MPs, PS-5000MPs, a mixture of PE, PP, and PS NPs (mass ratio = 1:1:1, denoted as NPs mixture) and a mixture of MPs (mass ratio = 1:1:1, denoted as MPs mixture) were prepared into suspensions in water with a concentration of 2 mg / mL using ultrapure water, and the suspensions were ultrasonically treated for 30 min;
[0087] (2) 15 mg of Fe3O4@PDA-HDTMS was added as an adsorbent into 10 mL of the above-mentioned PE-500NPs, PP-500NPs, PS-500NPs, PE-5000MPs, PP-5000MPs, PS-5000MPs, NPs mixture and MPs mixture suspensions, respectively, and stirred at 120 rpm for 30 min. Subsequently, the adsorbed MNPs and adsorbent were collected under an external magnetic field. The solid was dried in an oven at 60°C for 12 h and then weighed to obtain the total mass of Fe3O4@PDA-HDTMS and adsorbed MNPs.
[0088] (3) The adsorption efficiency of Fe3O4@PDA-HDTMS on MNPs was calculated using the following formula.
[0089]
[0090] Where m2 is the mass of the dried Fe3O4@PDA-HDTMS and adsorbed MNPs, m1 is the mass of the added Fe3O4@PDA-HDTMS, and C i is the initial concentration of the suspension containing MNPs, and V is the total volume of the suspension containing MNPs. The results are the average values obtained from three repeated experiments.
[0091] The results are as follows Fig.13 As shown, the removal rates of Fe3O4@PDA-HDTMS for PE-MPs, PP-MPs, and PS-MPs are 92.7% to 93.8%, with RSDs <5.5%; the removal rates for PE-NPs, PP-NPs, and PS-NPs are 82.2% to 87.2%, with RSDs <3.7%; in addition, the removal rates of the three MNPs of PE, PP, and PS after mixing are respectively at the micron level: 93.5%, RSD = 5.1%; and at the nano level: 84.8%, RSD = 0.9%.
[0092] Example 4 Removal of MNPs from bottled drinking water
[0093] Referring to the method of Example 3, the ultrapure water was replaced with bottled drinking water, and the bottled drinking water was used to prepare PE-500NPs, PP-500NPs, PS-500NPs, and a mixture of PE, PP, and PS NPs (mass ratio = 1:1:1) into a suspension in water with a concentration of 2 mg / mL;
[0094] The bottled water used was Wahaha, Nongfu Spring, Yibibao and Ice Dew; other parameters and conditions were consistent with those in Example 3.
[0095] The test results are as follows: the removal rate of Fe3O4@PDA-HDTMS for PE-500NPs, PP-500NPs, and PS-500NPs is 84.3% to 85.7%, and RSDs <4.2%; the removal rate for a mixture of PE, PP, and PS NPs is 85.0%, and RSD = 1.4%.
[0096] Example 5 Removal of MNPs in tap water
[0097] Referring to the method of Example 3, ultrapure water was replaced with tap water, and PE-500NPs, PP-500NPs, PS-500NPs, and a mixture of PE, PP, and PS NPs (mass ratio = 1:1:1) were prepared into a suspension in water with a concentration of 2 mg / mL using tap water;
[0098] Other parameters and conditions were consistent with those in Example 3. The test results showed that the removal rates of Fe3O4@PDA-HDTMS for PE-500NPs, PP-500NPs, and PS-500NPs were 84.3% to 85.8%, with RSDs < 2.3%; in addition, the removal rate of the mixture of PE, PP, and PS NPs was 84.7%, with RSD = 3.8%.
[0099] Example 6 Removal of MNPs in simulated seawater
[0100] Referring to the method of Example 3, ultrapure water was replaced with simulated seawater, and PE-500NPs, PP-500NPs, PS-500NPs, and a mixture of PE, PP, and PS NPs (mass ratio = 1:1:1) were prepared into a suspension in water with a concentration of 2 mg / mL using simulated seawater;
[0101] Other parameters and conditions were consistent with those in Example 3. The test results showed that the removal rates of Fe3O4@PDA-HDTMS for PE-NPs, PP-NPs, and PS-NPs were 73.2% to 76.3%, with RSDs < 3.8%; in addition, the removal rate of the mixture of PE, PP, and PS NPs was 74.8%, with RSD = 2.1%.
[0102] Comparative Example 1
[0103] Referring to the method of Example 3, the Fe3O4@PDA-HDTMS microspheres were replaced by Fe3O4 microspheres and Fe3O4@PDA microspheres, respectively, and the other parameters and conditions were consistent with those of Example 3.
[0104] The adsorption results are as follows Fig.14 ,from Fig.14 It can be seen that the adsorption efficiency of Fe3O4@PDA-HDTMS is significantly better than that of Fe3O4 and Fe3O4@PDA. Specifically, the removal efficiency of Fe3O4 for PE-500NPs, PP-500NPs, and PS-500NPs is 59.8% to 71.2%, and RSDs < 2.9%; the removal efficiency of Fe3O4@PDA for PE-500NPs, PP-500NPs, and PS-500NPs is 66.8% to 69.2%, and RSDs < 2.2%; the removal efficiency of Fe3O4@PDA-HDTMS for PE-500NPs, PP-500NPs, and PS-500NPs is 88.3% to 84.8%, and RSDs < 1.8%.
[0105] Comparative Example 2
[0106] Referring to the method of Example 3, the PE-500NPs, PP-500NPs, PS-500NPs, PE-5000MPs, PP-5000MPs, and PS-5000MPs in Example 3 were replaced by PE-10 μm, PP-10 μm, PS-10 μm, polyethylene terephthalate (PET)-10 μm, polyvinyl chloride (PVC)-10 μm, and polyamide (PA)-10 μm, and were respectively prepared into suspensions in water with a concentration of 2 mg / mL. The other parameters and conditions were consistent with those in Example 3.
[0107] The adsorption results are as follows Fig.15As shown, the removal rate of Fe3O4@PDA-HDTMS for PE-MPs, PP-MPs, and PS-MPs is 88.3% to 90.5%, and RSDs < 2.3%; the removal rate for PET-MPs, PVC-MPs, and PA-MPs is 73.8% to 75.5%, and RSDs < 2.2%. It can be found that the removal rate of Fe3O4@PDA-HDTMS for PE, PP, and PS plastics is better than that for PET, PVC, and PA plastics. This shows that Fe3O4@PDA-HDTMS can selectively adsorb PE, PP, and PS plastics.
[0108] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing a magnetic hydrophobic material Fe3O4@PDA-HDTMS for adsorbing MNPs, characterized in that: The preparation method comprises the following steps: (1) Preparation of Fe3O4 microspheres FeCl3·6H2O, ammonium acetate (NH4Ac), sodium citrate and ethylene glycol are mixed in a flask, and mechanically stirred to completely mix to obtain a yellow solution; the yellow solution is sealed in a high-pressure reactor to react; after the reaction, it is cooled, washed, magnetically separated and dried to obtain Fe3O4 microspheres; (2) Preparation of Fe3O4@PDA microspheres The magnetic Fe3O4 microspheres prepared in step (1) are added with Tris buffer, mechanically stirred, and then dopamine (DA) is added, and the reaction is continued by stirring, magnetic separation is performed, and the synthetic product Fe3O4@PDA is collected, washed, magnetically separated, and dried to obtain Fe3O4@PDA microspheres; (3) Preparation of Fe3O4@PDA-HDTMS microspheres HDTMS and the Fe3O4@PDA microspheres prepared in step (2) are added to a container containing a methanol solution and continuously stirred for reaction; the synthesized product is collected, washed, magnetically separated, and dried to obtain a magnetic hydrophobic material Fe3O4@PDA-HDTMS, i.e., Fe3O4@PDA-HDTMS microspheres.
2. The preparation method according to claim 1, characterized in that: The mass volume ratio of the Fe3O4@PDA microspheres and HDTMS in step (3) is 60:(0.45-0.6), mg:mL.
3. The magnetic hydrophobic material Fe3O4@PDA-HDTMS obtained by the preparation method described in any one of claims 1 and 2.
4. Use of the magnetic hydrophobic material Fe3O4@PDA-HDTMS according to claim 3 in removing pollutants from water.
5. A method for removing MNPs from water based on the magnetic hydrophobic material Fe3O4@PDA-HDTMS according to claim 3, characterized in that: The method is as follows: The magnetic hydrophobic material Fe3O4@PDA-HDTMS is placed in water for stirring, magnetic separation, and collection of the magnetic hydrophobic material Fe3O4@PDA-HDTMS.
6. The method according to claim 5, characterized in that The concentration of the magnetic hydrophobic material Fe3O4@PDA-HDTMS is 1.3-1.7 mg / mL.
7. The method according to claim 5, characterized in that The stirring conditions are: 20-30° C., 100-200 rpm, 20-40 min.
8. The method according to claim 5, characterized in that The separation is to separate the solid and liquid phases using an external magnet.
9. The method according to claim 5, characterized in that The MNPs include one or more of polystyrene, polyethylene and polypropylene plastics.
10. A method for improving the removal rate of polyethylene plastics and / or polypropylene plastics in water, characterized in that: The method is as follows: The magnetic hydrophobic material Fe3O4@PDA-HDTMS is placed in water for stirring, magnetic separation, and collection of the magnetic hydrophobic material Fe3O4@PDA-HDTMS.
Citation Information
Patent Citations
Preparation of ferromagnetic nanoparticle and application thereof in extraction and removal of micro-plastics
CN110237821A
Application of magnetic composite material in removal of plastic fragments
CN114314734A
Composite magnetic adsorption material as well as preparation method and application thereof
CN115055171A
Apparatus for magnetic separation of microplastics and method for magnetic separation of microplastics
WO2021261078A1
Preparation method for magnetic super-hydrophobic starch-based aerogel useful for oil-water separation
WO2023098009A1